2008
DOI: 10.1186/1471-2458-8-346
|View full text |Cite
|
Sign up to set email alerts
|

Breast and bowel cancer screening uptake patterns over 15 years for UK south Asian ethnic minority populations, corrected for differences in socio-demographic characteristics

Abstract: Background: A number of studies have reported low uptake of cancer screening programmes by South Asian populations in the UK. However, studies to date have not adjusted findings for differences in demographics and socio-economic status of these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
112
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 44 publications
(31 reference statements)
7
112
1
Order By: Relevance
“…27 Despite recent progress, breast cancer screening uptake remains much lower in South Asians than in non-South Asians. 28 Similarly, the pilot bowel cancer screening programme showed that uptake in South Asians was much lower than in non-South Asians. 28 We applied flexible models on all incident cancer cases in South Asians resident in England over a period of 19 years, enabling a more robust estimation of temporal and socioeconomic patterns in incidence than is possible with a solely descriptive approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Despite recent progress, breast cancer screening uptake remains much lower in South Asians than in non-South Asians. 28 Similarly, the pilot bowel cancer screening programme showed that uptake in South Asians was much lower than in non-South Asians. 28 We applied flexible models on all incident cancer cases in South Asians resident in England over a period of 19 years, enabling a more robust estimation of temporal and socioeconomic patterns in incidence than is possible with a solely descriptive approach.…”
Section: Discussionmentioning
confidence: 99%
“…28 Similarly, the pilot bowel cancer screening programme showed that uptake in South Asians was much lower than in non-South Asians. 28 We applied flexible models on all incident cancer cases in South Asians resident in England over a period of 19 years, enabling a more robust estimation of temporal and socioeconomic patterns in incidence than is possible with a solely descriptive approach. The assignment of South Asian ethnicity, however, differed between the cancer registrations and the general population, but SANGRA has been shown to have high sensitivity (89-96%) and specificity (94-98%) against self-assigned South Asian ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, utilization of breast cancer screening services is poor in South Asian women living in Asia (Maqsood et al, 2009;Bhatt et al, 2011;Grosse Frie et al, 2013), the US (Islam et al, 2006;Glenn et al, 2009;Lee et al, 2010) as well as other western countries (Sutton et al, 2001;Szczepura et al, 2008;Price et al, 2010;Rajan et al, 2011;Peltzer and Phaswana-Mafuya, 2014). Across the various studies among South Asians, the mammography rates range from 30-56%.…”
Section: Introductionmentioning
confidence: 99%
“…12,40,54 A single study on FS screening (an invasive form of bowel cancer screening not routinely used in the NHS BCSP at the time this research was conducted) identified specific cultural barriers associated with the threats to masculinity in African Caribbean men. 55 However, it is not known whether such barriers are also present in relation to gFOBt or if there are any culturally specific issues related to gFOBt screening among African Caribbean women.…”
Section: Introductionmentioning
confidence: 99%
“…12,[40][41][42] Low uptake of colorectal cancer (CRC) screening in the UK has continued to be identified in areas with higher ethnic diversity, 5,12 and within all South Asian religiolinguistic groups even when age, deprivation and gender are adjusted for. 40,43 We therefore also explored culturally specific barriers to uptake in South Asian communities to identify additional appropriate methods which could be specifically targeted at minority ethnic groups who speak English. To do this, we carried out interviews with 16 participants acting as 'key informants' on behalf of their communities.…”
Section: Introductionmentioning
confidence: 99%